Waveguide Propagation of Light in Polymer Porous Films Filled with Nematic Liquid Crystals - A. D. Kiselev; S. V. Pasechnik; D. V. Shmeliova; A. P. Chopik; D. A. Semerenko; A. V. Dubtsov (Advances in Condensed Matter Physics)
We theoretically analyze the waveguide regime of light propagation in a cylindrical pore of a polymer matrix filled with liquid crystals assuming that the effective radial optical anisotropy is biaxial. From numerical analysis of the dispersion relations, the waveguide modes are found to be sensitive to the field-induced changes of the anisotropy. The electrooptic properties of the polymer porous polyethylene terephthalate (PET) films filled with the nematic liquid crystal 5CB are studied experimentally and the experimental results are compared with the results of the theoretical investigation.